An attempt to re-balance the balanced scorecard towards a sustainable performance measurement system / Noel Yahanpath and Syrus Islam. - Yahanpath, Noel; Islam, Syrus (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
Despite the use of new performance measurement systems (PMSs), such as Balanced Scorecard (BSC), organisations worldwide have collapsed, leaving few clues before their collapse. So, two questions arise: ‘Why does it happen?’ and ‘How can it be addressed and resolved?’ The motivation of this research paper is to address these two questions. The study is a ‘multi-case study’ comprise of four cases for which the ‘documentary review procedure’ has been used to analyse data. For the development of theproposed model, this study used ‘analytic generalisation’ where BSC is used as our initial template. This study found that strong business performance can quickly be negated if the associated risk factors in achieving KPIs are not taken into account explicitly. It is also found that ignoring or paying insufficient attention to all relevant stakeholders in designing PMS makes an organisation more vulnerable to collapse. The basic limitation of case study research is applicable to this study. Further research can be carried out to test empirically the validation of our proposed model in different geographical settings. The study uncovers the underlying weakness of existing PMSs which fall short of meeting the challenges of the 21st century. Based on the balanced scorecard, our proposed Performance-Risk Linkage Model (PRLM) will have the potential to demonstrate a revamped conduit in strategic performance measurement systems, which will enable practitioners to get a competitive edge in managing the performance of complex organisations. This is one of the very few studies that examine the scope of the integration of key risk factors and all relevant stakeholders with performance measurement systems and, to our knowledge, the first of its kind in the Asia-Pacific Region.